Parenting Program in Overcoming the Negative Influence of Information Technology on Students - Saerozi, Imam; Supriyono, Supriyono; Haryanti, Nik; Marpuah, Siti (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The aim of the research is to describe the efforts and approaches of parenting programs in overcoming the negative influence of information technology at Islamic Vocational School 02 Durenan Trenggalek. The method used to conduct this research is based on the location of the data source, including the field research category, with a qualitative research type. The research design is a case study. Data collection methods use observation, interviews and documentation. Data analysis is carried out starting from data reduction, data presentation, and drawing conclusions. The results of the research show that the parenting program's efforts to overcome the negative influence of information technology on Class an and Al-Hadith. 2) Schools together with parents guide students to behave in a healthy direction which can help them choose alternative behavior that will bring maximum benefits to students in determining their choice of good social interactions, likes to help, loves the weak and respects other people. 3) School together with parents provides a good example. The approach taken by the parenting program in overcoming the negative influence of information technology on Class through a habituation approach to moral character, b) exemplary, by giving students an example to follow the example of the Prophet's morals, c) according to the characteristics of the student, even if possible, calling the parents and students to the office in order to successfully overcome these negative influences. 2) A group approach, namely: a) the school provides guidance in the guidance and counseling room to students who are negatively impacted by information technology, b) the school gathers students who violate school rules to provide counseling regarding the positive and negative benefits of information technology.